Respuesta :
the expression simplifies to
3(x+yi) +3i =9
x+yi =(9-3i)/3
x+yi= 3-i
3(x+yi) +3i =9
x+yi =(9-3i)/3
x+yi= 3-i
The complex number (x + yi) + (2(x + yi) + 3i) = 9 gives the value of x + yi as 3 - i
What is a complex number?
A complex number is a number of the form a + bi, where a and b are real numbers, and i = √-1
i² = (√-1)² = -1
Given the expression:
(x + yi) + (2(x + yi) + 3i) = 9
Hence:
x + yi + 2x + 2yi + 3i = 9
3x + 3yi + 3i = 9
3(x + yi + i) = 9
(x + yi + i) = 3
x + yi = 3 - i
The complex number (x + yi) + (2(x + yi) + 3i) = 9 gives the value of x + yi as 3 - i
Find out more on complex number at: https://brainly.com/question/10662770
#SPJ2